NOMENCLATURE OF THE STEROIDAL SAPOGENINS - ROSENKRANZ, G; DJERASSI, CARL (LABORATORIOS SYNTEX, CD. MEXICO, DF, MEX, 1963)
IN a recent communication, Klyne1 made the very timely suggestion that the present trivial nomenclature of cardiac aglucones, toad poisons and steroidal sapogenins be put on a more rational basis. It seems desirable to discuss thoroughly the various propo
NATURE
Keywords: NOMENCLATURE, STEROIDAL SAPOGENINS; MULTIDISCIPLINARIA; BIOQUIMICA; ESTEROIDES